Ethical Dilemma between Human Rights and State Sovereignty in Philosophical Dimension - Yunus, Nur Rohim (BULETIN ADALAH, 2024)
Human rights issues are often a driving factor for foreign intervention in a country's domestic affairs. However, this creates an ethical dilemma between state sovereignty and the protection of human rights. Countries accused of violating human rights often face international pressure and threats of intervention that could disrupt domestic stability.